Effects of GNSS Receiver Tuning on the PLL Tracking Jitter Estimation in the Presence of Ionospheric Scintillation. Issue 7 (8th July 2020) - Guo, K.; Aquino, M.; Vadakke Veettil, S.
Abstract: Ionospheric scintillation is an interference characterized by rapid and random fluctuations in radio frequency signals when passing through irregularities in the ionosphere. It can severely degrade the performance of Global Navigation Satellite System (GNSS) receivers, thus increasing positioning errors. Receivers with different tracking loop bandwidths and coherent integration times perform differently under scintillation. This study investigates the effects of GNSS receiver tracking loop tuning on scintillation monitoring and Phase Locked Loop (PLL) tracking jitter estimation using simulated GNSS data. The variation of carrier to noise density ratio ( C / N 0) under scintillation with different tracking loop settings is also studied. The results show that receiver tuning has a minor effect on scintillation indices calculation. The levels of C / N 0 are also similar for different PLL bandwidths and integration times. Additionally, the tracking jitter is estimated by theoretical equations and verified using the relationship with the PLL discriminator output noise, which is calculated using the post‐correlation measurements. Novel approaches are further proposed to calculate 1‐s scintillation index, which enables to compute the tracking jitter at a rate of 1 s. It is found that 1‐s tracking jitter can successfully represent the signal fluctuations levels caused by scintillation. This work is valuable for developing scintillation sensitive tracking error models and is also of great significance for GNSS receiver design to mitigate scintillation effects. Key Points: GNSS receiver PLL bandwidth and integration time tuning has a minor effect on scintillation indices and signal C / N 0 calculation A decrease in the bandwidth will decrease the PLL thermal noise but increase phase scintillation induced tracking jitter The 1‐s scintillation indices and tracking jitter successfully describe the signal distortions under scintillation